Mitch a rapidly evolving component of the Ndc80 kinetochore complex required for correct chromosome segregation in Drosophila - Williams, B (2007)
We identified an essential kinetochore protein, Mitch, from a genetic screen in D. melanogaster. Mitch localizes to the kinetochore, and its targeting is independent of microtubules (MTs) and several other known kinetochore components. Animals carrying mutations in mitch die as late third-instar larvae; mitotic neuroblasts in larval brains exhibit high levels of aneuploidy. Analysis of fixed D. melanogaster brains and mitch RNAi in cultured cells, as well as video recordings of cultured mitch mutant neuroblasts, reveal that chromosome alignment in mitch mutants is compromised during spindle formation, with many chromosomes displaying persistent mono-orientation. These misalignments lead to aneuploidy during anaphase. Mutations in mitch also disrupt chromosome behavior during both meiotic divisions in spermatocytes: the entire chromosome complement often moves to only one spindle pole. Mutant mitotic cells exhibit contradictory behavior with respect to the spindle assembly checkpoint (SAC). Anaphase onset is delayed in untreated cells, probably because incorrect kinetochore attachment maintains the SAC. However, mutant brain cells and mitch RNAi cells treated with MT poisons prematurely disjoin their chromatids, and exit mitosis. These data suggest that Mitch participates in SAC signaling that responds specifically to disruptions in spindle microtubule dynamics. The mitch gene corresponds to the transcriptional unit CG7242, and encodes a protein that is a possible ortholog of the Spc24 or Spc25 subunit of the Ndc80 kinetochore complex. Despite the crucial role of Mitch in cell division, the mitch gene has evolved very rapidly among species in the genus Drosophila.